Chapter 6 Unifying multiple identities through Arabic varieties An analysis of Arabic dialects in Kawaja Abdulqader's discourse - Zoghbor, Wafa (Taylor & Francis, 2022)
Language has a salient role of indicating group membership and is considered a symbol of different social identities. Within the Arabic language, variation across countries and regions create multiple identities, and the classification of Arabic into Standard Arabic (SA) and dialects has long created controversial positions about issues of belonging and intelligibility. This chapter explores representations of linguistic identities in the popular Arabic-medium television series Khawaja Abdulqader. The chapter uses discourse analysis (DA) to explore how the main character of the drama utilizes linguistic resources to reveal multiple identities of a non-Arab who speaks Arabic as a foreign language. Five extracts from the series are analysed with a focus on phonological and morphological features of three Arabic variations: Standard Arabic, Sudanese Dialect and Egyptian dialect. The chapter sheds light on the differences and similarities between the dialects as well as comparing these dialects with Gulf varieties such as the Emirati dialect. Based on the findings, the chapter argues that linguistic features and variation seen in the series unify rather than distance Arabic-speakers' identities and cultural belongingness.